Impact of left ventricular remodeling and function assessed by echocardiography in aortic valve stenosis - Dahl, Jordi Sanchez (Odense universitetshospital, 2019)
A thesis focusing on echocardiography and left ventricular remodeling in patients with aortic valve stenosis. Intended for professionals.
Keywords: kardiochirurgie; remodelace komor; Ventricular Remodeling; Aortic Valve Stenosis; Echocardiography; klinické lékařství; Clinical Medicine; aortální stenóza; Ventricular Function, Left; funkce levé komory srdeční; echokardiografie